Scientific fundamentals of building an innovative intelligent system of managing the production of entomophages - Chernova, I.; Lysenko, V. (Energy and Automation, 2024)
The article is devoted to the issue of improving information and technical support for the production of entomophages, in particular, the scientific foundations of building an innovative intelligent system for managing the production of entomophages. The purpose of the research is to develop the scientific basis for building an innovative intelligent system for controlling the production of entomophages. The object of research is the process of managing the production of entomophages. Research methods – structural synthesis, ontological-synergistic and neural network approaches, analysis of T. Saati hierarchies, Bayes network, cognitive and correlational analysis, computer modeling. An innovative intelligent control system for the production of the entomophagеs Habrobracon hebetor was developed based on the results of own research, the technological experience of specialists and modern methods of intellectual data analysis. The structure of the control system is presented. Management processes, software tools and management system innovations are displayed in the form of an associative map. An ontology of processes for innovative intelligent production management of the entomophage Habrobracon hebetor has been developed. The knowledge base of the innovative intelligent control system is presented in the form of facts and production rules. The results of the research increase the level of intellectualization of the processes of managing the production of entomophages, reduce the uncertainties in the management processes, increase the level of informatization and competence of the operator-technologist and are the basis for the development of a theory of decision-making in the production of biological means of plant protection. Key words: production of entomophages, intelligent management system, innovations, management processes